2019
DOI: 10.1681/asn.2018080815
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Proliferation of PD-1+ Kidney Double-Negative T Cells Is Dependent on Nonclassical MHC Proteins and IL-2

Abstract: Background CD4 2 CD8 2 double-negative (DN) ab T cells with innate-like properties represent a significant component of T cells in human and mouse kidneys. They spontaneously proliferate in the steady state and protect against ischemic AKI. However, the mechanisms regulating DN T cell homeostasis and responses to external danger signals from "sterile" inflammation remain poorly understood.Methods We used knockout mice, functional assays, and an established ischemic AKI model to investigate the role of various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 34 publications
1
35
1
Order By: Relevance
“…Interestingly though, in our hands murine renal DN T cells expressing Pd-1 are rare. Even though their frequency increases with ADPKD, we do not detect them at the same level as published by Sadasivam et al (16) (Figure 1C). This data may hint towards DN T cells having similar plasticity as other T cell subtypes where their phenotype, activation, and signaling is susceptible to microenvironmental stimuli.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…Interestingly though, in our hands murine renal DN T cells expressing Pd-1 are rare. Even though their frequency increases with ADPKD, we do not detect them at the same level as published by Sadasivam et al (16) (Figure 1C). This data may hint towards DN T cells having similar plasticity as other T cell subtypes where their phenotype, activation, and signaling is susceptible to microenvironmental stimuli.…”
supporting
confidence: 56%
“…However, other investigators have found different levels of this population. Zimmerman et al reported that only ~5% of all renal T cells are DN T cells in normal human kidney (15), and on the mouse side, renal DN T cells in 8-week-old wildtype C57Bl/6 mice have been reported to be either ~28% (16) or ~35% (14) of the total renal T cell population. While these discrepancies may be in part due to technical difficulties associated with studying DN T cells, which will be discussed later, it is likely that DN T cell frequency can change dependent on the age and strain of the mouse.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Krieg et al noticed that the stimulation of murine T-cells in presence of an agonistic BTLA antibody results in decreased IL-2 production and diminished occurrence of CD25 + T-cells (27). There is evidence from animal studies that BTLA knockout leads to autoimmune diseases (20,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the PD-1 subset is highly responsive under ischemia/reperfusion injury (IRI) conditions (100, 101). IL-2 is required for DN αβ cell activation and function as well as DN αβ cell proliferation during the steady state (101). In vitro T cell function is suppressed by DN αβ T cells (100).…”
Section: Cd4 + Il-22 + Cellsmentioning
confidence: 99%